CALCULATION OF THE BORING BAR DESIGN FOR STATIC RIGIDITY AND STRENGTH WITH SIMULTANEOUS BORING OF A STEPPED HOLE WITH FURTHER OPTIMIZATION - Karsakova, Nurgul; Sherov, Karibek; Donenbayev, Bakytzhan; Abulkhairov, Darmen; Sagynganova, Indira; Usserbayev, Muratbek; Teliman, Irina; Sherov, Aibek; Tussupbekova, Gulim (Journal of Applied Engineering Science, 2023)
A method for simultaneous processing of stepped holes in the bedding of a submersible pump and the boring bar design is proposed. The results of the study of existing methods for processing stepped holes and the design of boring tools are presented. It was revealed that the considered methods and designs of tools cannot be used for processing stepped holes in the submersible pump frame. The calculation of the developed design of the boring bar for static stiffness and strength, as well as the calculation of the stress-strain state (SSS) of the cutting plates by the finite element method using the ANSYS program, was carried out. The purpose of calculating the boring bar for static stiffness is a finite element study of the radial displacement of the boring bar cutter plates in the process of machining a stepped hole. As a result, the value of deformation in the axial and radial directions, which occur at the top of the cutting plate, is established. Also, the values of the cantilever overhang of the boring cutters are established, under which the conditions for the static rigidity of the boring bar are met. Taking into account the obtained results, the boring bar design was optimized.